2005
DOI: 10.1063/1.2065887
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale, unidirectional convection during phase separation of a density-matched liquid mixture

Abstract: Complete phase segregation may occur on a 10 cm scale even in the absence of buoyancy due to unidirectional, large-scale rapid bulk flow. Using a hexadecane-acetone nearly density-matched liquid mixture in a 20-cm-long condenser tube with a 1 cm diameter, we observed the rapid axial migration of the acetone-rich drops towards the warmer regions of the condenser. Conversely, the hexadecane-rich drops moved in the opposite direction, therefore ruling out thermocapillary effects as a possible explanation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Then, as soon as the nuclei reach a limit size of about 1 mm, which is approximately one-tenth the capillary length in the experiments by Califano and Mauri (2004) , they rapidly sediment, leading to an equilibrium state with two coexisting phases, within a time of about 10 s, in agreement with experimental observations ( Califano and Mauri, 2004;Califano et al, 2005 ).…”
Section: Mixing and Demixingsupporting
confidence: 78%
See 1 more Smart Citation
“…Then, as soon as the nuclei reach a limit size of about 1 mm, which is approximately one-tenth the capillary length in the experiments by Califano and Mauri (2004) , they rapidly sediment, leading to an equilibrium state with two coexisting phases, within a time of about 10 s, in agreement with experimental observations ( Califano and Mauri, 2004;Califano et al, 2005 ).…”
Section: Mixing and Demixingsupporting
confidence: 78%
“…As shown by Santonicola et al (2001) , this process is very slow, as after one hour the interfacial region is only a few millimeters thick. On the other hand, when the mixture is quenched back to 20 °C, the ensuing phase separation process is very rapid and a two-phase equilibrium state is reached within a few seconds ( Califano and Mauri, 2004;Califano et al, 2005 ). To explain this behavior, let us describe first the mixing process, assuming that the mixture is initially quiescent and phase separated (with > 2) along a flat interface at z = 0 , and is then instantaneously heated, so that < 2 at all times t ≥ 0.…”
Section: Mixing and Demixingmentioning
confidence: 99%
“…Mauri et al have examined many systems near consolute points and observed fluid flow caused by gradients in chemical potential (Poesio et al 2006;Gupta et al 1999;Santonicola et al 2001;Mauri et al 2003;Califano et al 2005;Lamorgese and Mauri 2005). Lamorgese and Mauri simulated a two-phase system quenched into the one-phase region and observed that convection coupled to diffusion via the body force slowed down mixing (Lamorgese and Mauri 2006).…”
Section: Introductionmentioning
confidence: 96%
“…8 Temperature-gradient effects on phase-separating binary liquid mixtures have been investigated in the past, both numerically [8][9][10] and experimentally. [11][12][13][14][15] In particular, Marangoni-like migration of droplets undergoing phase separation has been studied numerically under particular flow conditions, 10,16 although none of these works have focused on thermocapillary effects systematically. Other numerical studies [8][9][10] have focused on the effects of temperature gradients on diffusion-driven phase separation and, specifically, on how the morphology of a very viscous binary system, where both the molar and the thermal Peclet numbers of the mixture can be assumed to be negligible, evolves during phase separation with an imposed temperature gradient.…”
Section: Introductionmentioning
confidence: 99%